HARMONY OF TAḤSĪN - Nurlinda Sapitri; Adiyono Adiyono (Adisam Publisher, 2023)
The purpose of this study was to determine how the student's ability to read the Qur'an after learning tahsin control. This type of research is quantitative research. The population and samples used as the subject of this study were class X F MAN 1 Paser students totaling 30 students. This study used several techniques in data collection, namely, observation, tests, and documentation. Data processing uses validity and reliability test formulas, Product moment,